Temporal, spatial and tissue-specific expression of a myogenin-lacZ transgene targeted to the Hprt locus in mice - Vivian, J L (BioTechniques, 1999)
A lacZ transgene, expressed by the myogenin promoter, was introduced into the mouse hypoxanthine phosphoribosyltransferase (Hprt) locus by gene targeting in embryonic stem cells. Embryos between E10.5-E18.5 days were analyzed for expression of the transgene after staining for beta-galactosidase activity. Transgene expression was restricted to the skeletal muscle lineages reflecting a similar temporal and spatial pattern previously demonstrated for the endogenous myogenin gene. Additionally, a second transgene, MC1tk, showed expression in 87% of the clones when targeted to Hprt. This strategy, called targeted transgenesis, provides control for analyzing promoter sequences and for comparing various transgenes expressed by the same promoter